PERANCANGAN MEDIA PEMBELAJARAN ALAT TRANSPORTASI BERBASIS MULTIMEDIA - Hamid, Abdul; Khairiah, Khairiah (LPPM STMIK ANTAR BANGSA, 2016)
Ã‚Â Ã‚Â Abstract Ã¢â‚¬â€ Education is a major factor in the formation of the human person. In kindergarten not yet developed a curriculum-based creativity, they usually learn based on the theme. Theme introduction of means of transportation became one of the teaching learning activities. The purpose of learning the means of transport is to introduce the means of transportation to children.The purpose of this study is to establish a Learning Media Design Tools Multimedia Based Transportation using Adobe Flash Professional for kindergarten children as well as can be expected to know and understand about the tools transportation. With the Media Pebelajaran is expected children can receive lessons and with different learning media so that children are not saturated in the teaching and learning activities. Media Learning this as motivation and references other teachers in teaching with interactive techniques. The method used in this study is the system analyzing system requirements, design, code generation and testing.n as wireless or wifi (stand for wireless fidelity).Ã‚Â Intisari Ã¢â‚¬â€ Pendidikan merupakan faktor utama dalam pembentukan pribadi manusia. Pada anak-anak TK belum berkembangnya kurikulum berbasis kreativitas, biasanya mereka belajar berdasarkan pada tema. Tema pengenalan alat-alat transportasi menjadi salah satu KBM kegiatan pembelajaran. Tujuan pembelajaran alat-alat transportasi adalah mengenalkan alat-alat transportasi kepada anak. Tujuan penelitian ini adalah untuk membangun Perancangan Media Pembelajaran Alat-Alat Transportasi Berbasis Multimedia dengan menggunakan Adobe Flash Professional untuk anak-anak TK serta dapat diharapkan lebih mengerti dan memahami tentang alat-alat transportasi. Dengan adanya Media Pembelajaran ini diharapkan anak-anak bisa menerima pelajaran dengan baik dan dengan media pembelajaran yang berbeda agar anak-anak tidak jenuh dalam kegiatan belajar mengajar. Media Pembelajaran ini sebagai motivasi dan referensi guru-guru lain dalam mengajar dengan teknik yang interaktif. Metode yang digunakan dalam sistem penelitian ini adalah analisa kebutuhan sistem, desain, code generation, dan testing. Ã‚Â Kata Kunci Ã¢â‚¬â€ Media pembelajaran, Multimedia, Interaktif, Alat Transportasi.